The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/jor.20743
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of polyethylene tibial insert damage from in vivo function and in vitro wear simulation

Abstract: Function and wear of total knee arthroplasties were compared by analysis of damage patterns on polyethylene tibial inserts retrieved from patients (Group R) with inserts obtained after in vitro force-controlled knee joint wear simulation. Two simulator input profiles were evaluated, including standard walking (Group W), and combined walking and stair descent (Group W þ S), simulating varied activities and a more severe physiological environment. Damage regions on all inserts were quantitatively assessed. On av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
60
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 68 publications
(142 reference statements)
12
60
3
Order By: Relevance
“…This study supports previous studies showing that damage patterns evident on polyethylene inserts after knee joint wear simulation under-predict damage observed on retrieved inserts [6,11]. Such disparity has been attributed to discrepancies between the simulators' articular contact mechanics [3][4][5][6][7][8][9][10][11] and variations in surface abrasion and lubrication [37,38] compared with the physiological conditions existing in vivo after knee joint replacement.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study supports previous studies showing that damage patterns evident on polyethylene inserts after knee joint wear simulation under-predict damage observed on retrieved inserts [6,11]. Such disparity has been attributed to discrepancies between the simulators' articular contact mechanics [3][4][5][6][7][8][9][10][11] and variations in surface abrasion and lubrication [37,38] compared with the physiological conditions existing in vivo after knee joint replacement.…”
Section: Discussionsupporting
confidence: 87%
“…Such disparity has been attributed to discrepancies between the simulators' articular contact mechanics [3][4][5][6][7][8][9][10][11] and variations in surface abrasion and lubrication [37,38] compared with the physiological conditions existing in vivo after knee joint replacement. Possible explanations for the observed differences between the explanted and simulated UKR in the current study are that the short duration of simulated loading and range of motion did not fully represent the variety of conditions endured by the UKR during daily living activities.…”
Section: Discussionmentioning
confidence: 96%
“…Wear simulator studies have been shown to be a powerful tool in predicting the wear performance of artificial joints for TKR and THR [16][17][18][19]. However, only a few studies have dealt with experimental wear studies on TAR [20][21][22].…”
Section: Introductionmentioning
confidence: 98%
“…Subsequently, the circumference of both the insert periphery and the wear scars were digitised on calibrated digital images of the articular surface using published photogrammetry methods. 12,13 The insert circumference was used to map these data to the tibial model coordinate system.…”
Section: Methodsmentioning
confidence: 99%